The contribution of risk factors to the higher incidence of invasive and in situ breast cancers in women with higher levels of education in the European prospective investigation into cancer and nutrition. - Menvielle, G; Kunst, A; Gils, v; Peeters, P; Boshuizen, H; Overvad, K; Olsen, A; Tjonneland, A; Hermann, S; Kaaks, R; Bergmann, M; Illner, A; et al. (2011)
The authors investigated the role of known risk factors in educational differences in breast cancer incidence. Analyses were based on the European Prospective Investigation Into Cancer and Nutrition and included 242,095 women, 433 cases of in situ breast cancer, and 4,469 cases of invasive breast cancer. Reproductive history (age at first full-term pregnancy and parity), exposure to endogenous and exogenous hormones, height, and health behaviors were accounted for in the analyses. Relative indices of inequality (RII) for education were estimated using Cox regression models. A higher risk of invasive breast cancer was found among women with higher levels of education (RII = 1.22, 95% confidence interval (CI): 1.09, 1.37). This association was not observed among nulliparous women (RII = 1.13, 95% CI: 0.84, 1.52). Inequalities in breast cancer incidence decreased substantially after adjusting for reproductive history (RII = 1.11, 95% CI: 0.98, 1.25), with most of the association being explained by age at first full-term pregnancy. Each other risk factor explained a small additional part of the inequalities in breast cancer incidence. Height accounted for most of the remaining differences in incidence. After adjusting for all known risk factors, the authors found no association between education level and risk of invasive breast cancer. Inequalities in incidence were more pronounced for in situ breast cancer, and those inequalities remained after adjustment for all known risk factors (RII = 1.61, 95% CI: 1.07, 2.41), especially among nulliparous women.